Investigation of the sliding behavior between steel and mortar for seismic applications in structures. - McCormick, Jason
The friction developed between a steel base plate and a mortar base contributes shear resistance to the building system during a seismic event. In order to investigate the possible sliding behavior between the base plate and the mortar, a shake table study is undertaken using a large rigid mass supported by steel contact elements which rest on mortar surfaces connected to the shake table. Horizontal input accelerations are considered at various magnitudes and frequencies. The results provide a constant friction coefficient during sliding with an average value of approximately 0.78. A theoretical formulation of the friction behavior is also undertaken. The theoretical equations show that the sliding behavior is dependent on the ratio of the friction force to the input force. The addition of vertical accelerations to the system further complicates the sliding behavior as a result of the varying normal force. This results in a variable friction resistance which is a function of the amplitude, phase, and frequency of the horizontal and vertical input motions. In general, this study showed a consistent and reliable sliding behavior between steel and mortar.
Keywords: Friction; Steel; Mortar; Steel structures; Shake table tests; Seismic